The Role of The World Bank to Support Economic in Timor-Leste - da Costa, Acio; Mareila Seixas Miranda; Shuai Tong; Gunawan, Cakti Indra (International Journal of Management and Business, 2025)
This research discusses the role of the World Bank in supporting the economic development of Timor-Leste, a small country that faced significant economic challenges post-independence in 2002 As one of the youngest countries in the world, Timor-Leste relies on oil and gas as its main source of income, which creates big risks when those resources are reduced. The World Bank has played an important role in helping diversify the economy and improving the quality of public services through project funding, technical consulting, and strengthening institutions. This article uses a qualitative method with a descriptive approach, utilizing secondary data from World Bank annual reports, government statistics, and academic literature. The main focus is on the education, infrastructure and governance sectors. The research results show that World Bank interventions have improved human development indicators, improved basic infrastructure, and strengthened government governance capacity. However, challenges such as dependence on natural resources and weak institutional capacity remain significant obstacles. In conclusion, World Bank support has had a considerable positive impact on Timor-Leste's economic development, although program sustainability requires strengthening local capacity. This research's recommendations include economic diversification, empowering local institutions, and developing more sustainable funding strategies